MicroRNAs, New Players in the Plant–Nematode Interaction - Jaubert-Possamai, Stéphanie; Noureddine, Yara; Favery, Bruno (Frontiers in Plant Science, 2019)
Plant-parasitic root-knot and cyst nematodes are microscopic worms that cause severe damage to crops and induce major agricultural losses worldwide. These parasites penetrate into host roots and induce the formation of specialised feeding structures, which supply the resources required for nematode development. Root-knot nematodes induce the redifferentiation of five to seven root cells into giant multinucleate feeding cells, whereas cyst nematodes induce the formation of a multinucleate syncytium by targeting a single root cell. Transcriptomic analyses have shown that the induction of these feeding cells by nematodes involves an extensive reprogramming of gene expression within the targeted root cells. MicroRNAs are small non-coding RNAs that act as key regulators of gene expression in eukaryotes by inducing the post-transcriptional silencing of protein coding genes, including many genes encoding transcription factors. A number of microRNAs displaying changes in expression in root cells in response to nematode infection have recently been identified in various plant species. Modules consisting of microRNAs and the transcription factors they target were recently shown to be required for correct feeding site formation. Examples include miR396 and GRF in soybean syncytia, and miR159 and MYB33 in Arabidopsis giant cells. Moreover, some conserved microRNA/target modules seem to have similar functions in feeding site formation in different plant species. These microRNAs may be master regulators of the reprogramming of expression occurring during feeding site formation. This review summarises current knowledge about the role of these plant microRNAs in plant-nematode interactions.